Biomechanical analysis to determine the muscular intervention of ballistic stretching - K. Gianikellis; A. Vara Gazapo; A. Bote García; J. R. Muñoz Cruz (Asociación Española de Ciencias del Deporte, 2010)
The aim of stretching exercises is to increase muscle-tendon flexibility which depends on neurogenics (stretch reflex), myogenics (viscoelasticity of the musculo-tendinous structures) and joint constraints. The main purpose of this study was to determine the intervention of the muscles quadriceps femoris (rectus femoris - vastus medialis) and biceps femoris and its relationship with the kinematics of the hip joint during a common ballistic stretching exercise. Kinematic data of the hip joint and EMGraphic data of the muscles quadriceps femoris (rectus femoris -vastus medialis) and biceps femoris were recorded by a measurement chain which consists of an EMG synchronized with an ELGoniometric system. The study yielded information concerning the sequence of muscular activation and the history of the angular velocity and acceleration of the hip joint during the defined phases of acceleration and deceleration of the flexion-extension movements. The obtained results confirmed statistically significant (p < .000 -p < .05) linear correlations (.902 -.504) between the kinematic, temporal and spectral parameters of the EMG data. KEY WORDS: flexibility-training, ballistic stretching, EMG.